Phosphorus Retention and Remobilization in Vegetated Buffer Strips: A Review - Roberts, William M.; Stutter, Marc I.; Haygarth, Philip M. (Journal of environmental quality, 2012)
Diffuse pollution remains a major threat to surface waters due to eutrophication caused by phosphorus (P) transfer from agricultural land. Vegetated buffer strips (VBSs) are increasingly used to mitigate diffuse P losses from agricultural land, having been shown to reduce particulate P transfer. However, retention of dissolved P (DP) has been lower, and in some cases VBSs have increased delivery to surface waters. The aims of this review were (i) to develop a conceptual model to enhance the understanding of VBS functioning in terms of DP, (ii) to identify key processes within the model that affect DP retention and delivery, and (iii) to explore evidence for the controls on these processes. A greater understanding in these areas will allow the development of management strategies that enhance DP retention. We found evidence of a surface layer in buffer strip soils that is enriched in soluble P compared with adjacent agricultural land and may be responsible for the reported increased DP delivery. Through increased biological activity in VBSs, plants and microorganisms may assimilate P from particulates retained in the VBSs or native soil P and remobilize this P in a more soluble form. These conclusions are based on a limited amount of research, and a better understanding of biogeochemical cycling of P in buffer strip soils is required.